(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
For the purpose of preparing children for a society that is becoming increasingly knowledge-driven and digitally linked, the incorporation of technology into primary education has become an increasingly prominent strategic focus. The purpose of this study paper was to conduct an in-depth analysis of the feasibility and acceptability of educational technological development in primary schools in India, with a particular emphasis on coeducational institutions that are controlled by Mandal Parishads and Municipalities in the state of Kerala. Using a variety of theoretical frameworks and best practices from around the world, including the SAMR model, the TPACK framework, and the Diffusion of Innovation theory, the research investigated the ways in which educational technology might be meaningfully integrated into the teaching and learning processes. The purpose of this article was to identify important human and institutional hurdles that impact technology integration. This was accomplished by a comprehensive analysis of secondary data sources, which included information from government reports, literature that had been peer-reviewed, and implementation evaluations. The lack of digital literacy among educators, opposition to change, poor infrastructure, and uneven policy implementation were some of the characteristics that were identified. Evaluations were conducted on Kerala’s initiatives, such as the KITE and the Hi-Tech School Project, in order to get a better understanding of the advantages and disadvantages of state-led interventions. Although Kerala has made tremendous progress in providing schools with digital tools and training, there are still issues to be faced in terms of inequities in the deployment of these technologies between urban and rural areas, as well as in terms of teacher preparation and content accessibility. The paper The need of localised digital material, context-sensitive teacher training, and public-private partnerships to address infrastructural gaps was also emphasised in the presentation, which also included an outline of future prospects for policy and research. For the purpose of ensuring the long-term sustainability and equality in the deployment of educational technology across India, strategic policy proposals were made. Based on the findings of the study, it was determined that a strategy that is collaborative, linked with policy, and informed by research is necessary for the successful and inclusive integration of technology in primary education. It is imperative that special emphasis be paid to the improvement of equity, consistency, and relevance, particularly in government school sectors that are under-represented.